Where's home mummy? : a migrant's story - Barker, Hazel (Burleigh, Qld. : Zeus, 2004)
Traces the lives of Colin Richard Barker and his parents who immigrate to Australia in the late 1940's. The story covers the family's struggles with life in rural Victoria.
Keywords: Immigrants -- Victoria -- Biography; English -- Victoria -- Biography